Meranti Island E-Government Master Plan: A Root Cause and SWOT Analysis - Tenia Wahyuningrum; Gita Fadila Fitriana; Arief Rais Bahtiar; Aina Azalea Ardani; Imelda Imelda; Teotino Gomes Soares (Indonesian Journal of Information Systems, 2023)
The government has established a development program for the development of Information and Communication Technology with the term e-government. The implementation of e-government in government governance and public services certainly requires the use of information and communication technology (ICT) along with reliable human resources to manage it. There is still a reasonably high gap between the EBGS maturity level of the central agency and the index, and the local government is a challenge for the Meranti Islands Regency. To realize its vision and mission, the Meranti Islands Regency has made various efforts for transparency, accountability, good governance, and efficiency of government administration supported through ICT. The purpose of this research is the mapping of ICT utilization data in Meranti Islands Regency and the results of the identification of the obstacles that occur using GAP Analysis. GAP analysis uses Root Cause Analysis (RCA) and SWOT analysis for its analysis. The GAP analysis results show that based on the SWOT analysis, 18 strengths, 19 weaknesses, 12 opportunities, and 12 thread ats in the application of ICT are obtained, which are divided into 6 components. Based on the Root Cause Analysis, it was found that the main problem was caused by the low capacity of human resources in the application of ICT, as well as insufficient hardware/software requirements. For the study results study, it can be concluded that a SWOT analysis equipped with Root Cause Analysis can be used for strategic planning for implementing EBGS in the next fiveyears.